The Politics of Conflict Resolution: Negotiating Public Policy Amidst Community Dissonance - Nahruddin, Zulfan (Journal of Public Representative and Society Provision, 2022)
This study investigates the politics of conflict resolution within the context of public policy negotiation, particularly in environments marked by community dissonance. Using a qualitative research methodology, the study explores the strategies and approaches employed to mediate conflicts and disputes that arise during policy development and implementation. The findings reveal that successful negotiation of public policy in discordant communities hinges on several key factors: active stakeholder participation, inclusive decision-making processes, addressing power imbalances, effective communication, and the allocation of sufficient resources. These insights underscore the critical importance of considering diverse perspectives and interests in policy formulation and enactment. The research contributes to the existing body of literature on public policy negotiation in contentious settings and offers practical strategies for achieving equitable and effective policy outcomes.